Numerical calculation of phase change heat conduction in freezing soil by lattice Boltzmann method based on enthalpy method - Tian, Lin; Shen, Linfang; Wang, Zhiliang; Luo, Junyao (Frontiers in Earth Science, 2023)
In the freezing process, the soil is accompanied by heat conduction, heat release for ice-water phase change, phase change interface movement, and a change in thermal diffusion coefficient, which is a complex nonlinear problem and is hard to solve. This study uses the enthalpy method to establish a unified control equation for heat conduction in the entire calculation region (including the solid-phase zone, liquid-phase zone, and phase change interface). It solves the equation numerically, relying on the D2Q4 model of the lattice Boltzmann method, and determines the evolution of the temperature field and solid-liquid phase change interface position with time. The trends in the soil’s temperature field evolution and freezing front movement under unilateral and bilateral cold sources are discussed using an example from an artificial freezing project. The results show that when −10°C is taken as the limit for freezing wall temperature, the freezing wall thickness developed at 5, 10, 20, 30, and 40 days under the unilateral cold source is 0.24, 0.33, 0.47, 0.57, and 0.66 m, respectively. The overall temperature in the soil drops below −13.6°C and −26.4°C at 35 days and 45 days under the bilateral cold sources. These values can provide a basis for engineering design.